The Premium for risk as a Determinant of Interest Rates in Underdeveloped Rural Areas: Comment - Chandavarkar, A. G. (Quarterly Journal of Economics, 1965)
Journal Article The Premium for Risk as a Determinant of Interest Rates in Underdeveloped Rural Areas: Comment Get access A. G. Chandavarkar A. G. Chandavarkar Reserve Bank of India, Bombay Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 79, Issue 2, May 1965, Pages 322–325, https://doi.org/10.2307/1880637 Published: 01 May 1965